2018
DOI: 10.1002/aqc.2947
|View full text |Cite
|
Sign up to set email alerts
|

The effect of regional sea surface temperature rise on fisheries along the Portuguese Iberian Atlantic coast

Abstract: The environmental effects of climate change are expected to impact fisheries, and related economies, and represent a significant challenge for the development of government policy. The impact of ocean warming on fisheries yields is of particular concern. The effect of sea surface temperature (SST) on fisheries in three distinct biogeographic areas (north‐western, NW; south‐western, SW; and south, S) and different fleet sectors (trawl, seine, and multi‐gear) of the Portuguese coast was examined. The mean temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
(84 reference statements)
3
6
1
Order By: Relevance
“…Further, some species, such as sardine, may prefer colder waters for their reproductive and feeding dynamics (Sabatés et al, 2006), and increase in SST values could favour species associated with warmer waters. Hence, a general increase in SST can negatively affect fisheries catches by changing the catch composition (Leitão et al, 2018). The results of our study showed similar associations between NPP, SST, and the catches of the investigated fish species.…”
Section: Discussionsupporting
confidence: 80%
“…Further, some species, such as sardine, may prefer colder waters for their reproductive and feeding dynamics (Sabatés et al, 2006), and increase in SST values could favour species associated with warmer waters. Hence, a general increase in SST can negatively affect fisheries catches by changing the catch composition (Leitão et al, 2018). The results of our study showed similar associations between NPP, SST, and the catches of the investigated fish species.…”
Section: Discussionsupporting
confidence: 80%
“…In the northern Beibu Gulf, the massive reclamation and embankment activities in the eastern Qinzhou Bay have compromised interchange between seawater and inland discharges, decreasing regional productivity and facilitating SST increase (Wu et al, unpublished data). These changes can further impact local ecosystem regimes, including accumulating inland pollutants (Dr Bing Gong, personal communication), forming a hypoxic region on warm‐weather days (Dr Haiping Wu, unpublished data), and gradual shift in prey composition (Leitão, Maharaj, Vieira, Teodósio, & Cheung, ; Potts et al, ). HPA planning needs to consider measures mitigating ecosystem deterioration or, more proactively, restoring damaged habitat.…”
Section: Discussionmentioning
confidence: 99%
“… 11 for an opposite trend 12 ). These environmental changes are likely to lead to consequences for the main fisheries of Portugal, including changes in the catch composition by the introduction of subtropical species 13 , or fluctuations of landings due to environmental changes with mechanistic consequences on the recruitment of small and medium pelagics 14 18 also found a general decreasing trend of landings of species with affinity for temperate waters and an opposite trend for species with affinity for subtropical/tropical waters, evidencing that species might respond differently to climate change due to their ecology and biology. A big effort to understand the effect of environmental variables on marine fish landings has been paid in recent years (e.g.…”
Section: Introductionmentioning
confidence: 99%